Development of human digestive organ media based on Assemblr EDU - Arnelia Dwi Yasa; Farida Nur Kumala; Rujian Nur Andi Alfianto; Moh Salimi (Inovasi Kurikulum, 2024)
This study focuses on developing and evaluating a new learning media called Assemblr EDU-based human digestive organs media for elementary science learning. The motivation behind this research is the limitation of current learning materials, such as books and worksheets, which hinder students' understanding of the subject. The ADDIE development research model is employed, with 5th-grade students as the subjects. The study utilizes descriptive data analysis techniques and collects data through questionnaires using a Likert scale. The media is evaluated by material experts, media experts, linguists, teachers, and students. The results reveal that the media is considered feasible, with 88.5 percent of media experts rating it as "Very Feasible," 90 percent of material experts evaluating it as "Very Feasible," and 62.5 percent of linguists considering it as "Feasible." Furthermore, a practicality test conducted with teachers and students shows a 90 percent positive response. The effectiveness test, assessed through a t-test, demonstrates significant improvement in learning outcomes. Overall, the Assemblr EDU-based human digestive organ media proves feasible, practical, and effective in enhancing learning in elementary science. AbstrakKeterbatasan media pembelajaran khususnya pada pembelajaran IPA yang hanya menggunakan buku dan LKS saja tentang organ pencernaan manusia menyebabkan siswa kurang memahami materi yang disampaikan, sehingga pengembangan media pembelajaran perlu dilakukan. Tujuan penelitian ini untuk mendeskripsikan pengembangan media alat pencernaan manusia berbasis Assemblr EDU pada pembelajaran IPA SD serta mengetahui kelayakan, kepraktisan dan keefektifan media tersebut. Penelitian ini menggunakan model penelitian pengembangan ADDIE dengan subjek penelitian kelas 5 Sekolah Dasar. Penelitian ini menggunakan teknik analisis data deskriptif, dengan angket menggunakan skala likert oleh ahli materi, ahli media, ahli bahasa, serta respon guru dan siswa untuk pengumpulan data. Berdasarkan analisis data, hasil penelitian menunjukkan validasi ahli media menilai penggunaan media ini layak digunakan dengan hasil akhir 88,5 persen dinilai “Sangat Layak”, validasi ahli materi 90 persen dinilai “Sangat Layak”, dan validasi ahli bahasa 62,5 persen dinilai “Layak”. Sedangkan, uji praktikalitas diperoleh dari angket respon guru dan siswa mencapai 90 persen. Uji efektivitas yang dinilai melalui uji-t menunjukkan peningkatan hasil belajar yang signifikan. Media organ pencernaan manusia berbasis Assemblr EDU pada pembelajaran IPA SD layak, praktis dan efektif dalam meningkatkan pembelajaran.Kata Kunci: Assemblr EDU; organ pencernaan manusia; IPA